Lichenoid vulvar disease: A review - R. Fruchter, BA; L. Melnick, MD; M.K. Pomeranz, MD (Wolters Kluwer, 2017)
Vulvar dermatoses are common, potentially debilitating conditions that can be seen by a variety of medical specialists. Lichenoid vulvar diseases, namely lichen sclerosus (LS), lichen planus (LP), and lichen simplex chronicus (LSC), can all negatively impact patients' quality of life and LS and LP also have an association with squamous cell carcinoma. It is essential that dermatologists are familiar with the unique features of each of these conditions to ensure the appropriate management and follow up. Herein, we provide an update on the epidemiology, clinical presentation, histopathology, and treatment of patients with vulvar LS, LP, and LSC. Keywords: lichenoid vulvar disease, vulvar dermatoses, lichen sclerosus, lichen planus, erosive lichen planus, lichen simplex chronicus